The innovation engine for growth : an actionable roadmap to thriving in a hyper-competitive world - Mazumdar, Sanjay K.; Perkins, Cheryl A. (New York, NY : Routledge, 2022)
Written by experts on innovation and growth, this book provides the necessary tools to systematically develop and sustain profitable innovation pipelines. In a hypercompetitive global market, businesses must innovate to survive; yet the failure rate for innovation is extremely high. Strategists and thought leaders, Cheryl Perkins and Dr. Sanjay Mazumdar, offer a sophisticated yet practical approach for implementing successful innovation. Leveraging thought-provoking questions and powerful templates, the book outlines how companies can leverage core strengths, build internal innovation capabilities, partner effectively, and identify the promising areas to pursue. In addition, the book highlights emerging innovations in several major industries, providing fodder to fuel creative thinking and exploration of possible applications across a variety of different industries. Managers and leaders will welcome the innovation insights and examples, as well as the templates to build an organization's plan to diagnose patterns of innovation, identify opportunities, and apply emerging innovations in their own industries and businesses.
"Written by experts on innovation and growth, this book provides the necessary tools to systematically develop and sustain profitable innovation pipelines. In a hypercompetitive global market, businesses must innovate to survive, yet the failure rate for innovation is extremely high. Strategists and thought leaders, Cheryl Perkins and Dr Sanjay Mazumdar, offer a sophisticated yet practical approach for implementing successful innovation. Leveraging thought-provoking questions and powerful templates, the book outlines how companies can leverage core strengths, build internal innovation capabilities, partner effectively, and identify the promising areas to pursue. In addition, the book highlights emerging innovations in several major industries, providing fodder to fuel creative thinking and exploration of possible applications across a variety of different industries. Managers and leaders will welcome the innovation insights and examples, as well as the templates to build an organization's plan to diagnose patterns of innovation, identify opportunities, and apply emerging innovations in their own industries and businesses"-- Provided by publisher.
OCLC-licensed vendor bibliographic record.
Keywords: Technological innovations -- Economic aspects; Diffusion of innovations; Success in business; BUSINESS & ECONOMICS / Strategic Planning; BUSINESS & ECONOMICS / Leadership; BUSINESS & ECONOMICS / Development / Business Development